2023
DOI: 10.3390/jcm12062348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiofrequency Diathermy Plus Therapeutic Exercises on Pain and Functionality of Patients with Patellofemoral Pain Syndrome: A Randomized Controlled Trial

Abstract: Although consensus has been reached about the use of therapeutic exercise in patellofemoral pain syndrome, several techniques used worldwide such as radiofrequency diathermy could be useful as complementary therapy. The objective of this randomized controlled trial was to compare the effects of adding radiofrequency diathermy to therapeutic exercises in patients with patellofemoral pain syndrome. Fifty-six participants were randomly assigned either to radiofrequency diathermy plus therapeutic exercises group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…The modest improvements observed in this study in the control group could point out that more than a month of intervention with therapeutic knee exercises is needed to obtain the appropriate results. The pain relief experienced by participants of radiofrequency diathermy group could have facilitated their exercise performance, allowing them to obtain greater improvements in knee function, their range of movement and lower limb function, as was observed in previous studies [35]. This explanation agrees with the study of Kumaran and Watson (2019), in which 19 points of improvement on the WOMAC were obtained in knee osteoarthritis patients treated with radiofrequency diathermy added to exercises while poor results were observed in the control group [8].…”
Section: Discussionsupporting
confidence: 86%
“…The modest improvements observed in this study in the control group could point out that more than a month of intervention with therapeutic knee exercises is needed to obtain the appropriate results. The pain relief experienced by participants of radiofrequency diathermy group could have facilitated their exercise performance, allowing them to obtain greater improvements in knee function, their range of movement and lower limb function, as was observed in previous studies [35]. This explanation agrees with the study of Kumaran and Watson (2019), in which 19 points of improvement on the WOMAC were obtained in knee osteoarthritis patients treated with radiofrequency diathermy added to exercises while poor results were observed in the control group [8].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have demonstrated the efficacy of 4.4 MHz RF diathermy in managing pain, such as low back pain and shoulder pain [ 9 , 10 ]. While there have been studies on RF diathermy for KOA, the frequencies applied in each study have varied [ 11 , 12 , 13 , 14 ]. However, there are still not enough prospective studies performed to investigate the effectiveness of 4.4 MHz RF diathermy in treating KOA.…”
Section: Introductionmentioning
confidence: 99%